(untitled) (Journal of Organizational Psychology, 2017)
Public sector organizations within multi-ethnic settings are facing the challenge of ethnic tension. One of the measures adopted globally to mitigate these tensions in the public sector is the implementation of representative bureaucracies that mirror ethnic composition within society. Although this measure has been successful to some extent, studies suggest that there is increasing tension arising from ethnic discrimination. This review paper charts a new course in psychological ownership perception and representative bureaucracy theories by attempting to establish a link between ethnic representation and employee’ ownership perception. Propositions based on a critical review of existing literature are presented to enable further empirical investigations.